Masculinities in psychotherapy: a fundamental approach to treating men prosecuted for violence against women - Ochoa Cerrón, Victor Eduardo (2025)
The objective of this study was to identify the perceptions of psychotherapists working at the Institutional Care Centers (CAI) of the Peruvian Ministry of Women and Vulnerable Populations (MIMP) regarding their work with men prosecuted for committing violence against women. A qualitative approach with a phenomenological design was used, employing semi-structured interviews administered to psychotherapists working at CAI centers located in Lima, Callao, Ayacucho, and Cusco. Among the main findings, it is noteworthy that addressing masculinities from a gender perspective is perceived as a crucial component in psychotherapeutic intervention with aggressors. This therapeutic model helps participants recognize and take responsibility for their actions, challenge stereotypes of masculinity that legitimize violence, and develop skills for anger management and emotional expression, thereby improving their role as parents and their relationships with family members and partners.